A lot of people are saying : the new conspiracism and the assault on democracy - Muirhead, Russell, 1965-; Rosenblum, Nancy L. (Nancy Lipton), 1947- (Princeton University Press, 2020)
How the new conspiracists are undermining democracy-and what can be done about itConspiracy theories are as old as politics. But conspiracists today have introduced something new-conspiracy without theory. And the new conspiracism has moved from the fringes to the heart of government with the election of Donald Trump. In A Lot of People Are Saying, Russell Muirhead and Nancy Rosenblum show how the new conspiracism differs from classic conspiracy theory, how it undermines democracy, and what needs to be done to resist it.